(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article explores speech clichés as ready-made formulas of thought formed within a language, analyzing their connection to human cognition, perception processes, and national mentality. The semantic and structural characteristics of clichés are examined, and expressive versus cognitive approaches to them are compared. Drawing on the views of Z. Hamavand, J. Shults, and A. Polger, the author highlights the role of clichés as linguistic units and discusses their compositional and non-compositional properties. It is emphasized that clichés are deeply embedded in the background knowledge, serving as psychological and communicative ready-made units, and their usage and interpretation are closely tied to the conceptual structure of a given language.